2014
DOI: 10.1152/ajprenal.00294.2013
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-9 ameliorates anti-GBM glomerulonephritis by inhibiting Th1 and Th17 immune responses in mice

Abstract: Antiglomerular basement membrane glomerulonephritis (anti-GBM GN) is a Th1- and Th17-predominant autoimmune disease. Galectin-9 (Gal-9), identified as the ligand of Tim-3, functions in diverse biological processes and leads to the apoptosis of CD4(+)Tim-3(+) T cells. It is still unclear how Gal-9 regulates the functions of Th1 and Th17 cells and prevents renal injury in anti-GBM GN. In this study, Gal-9 was administered to anti-GBM GN mice for 7 days. We found that Gal-9 retarded the increase of Scr, ameliorat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 36 publications
3
40
0
Order By: Relevance
“…Of note, although the anti-GBM model resulted in significant albuminuria in both control and podFcRn KO mice, the percentage of crescents seen in the control mice was relatively low. These findings are in accord with some other studies of this model in mice, (49)(50)(51)(52) making this model less ideal to study immune mediated kidney disease.…”
Section: Podocyte-specific Ko Of Fcrn Did Not Alter Neutrophil Invasisupporting
confidence: 89%
“…Of note, although the anti-GBM model resulted in significant albuminuria in both control and podFcRn KO mice, the percentage of crescents seen in the control mice was relatively low. These findings are in accord with some other studies of this model in mice, (49)(50)(51)(52) making this model less ideal to study immune mediated kidney disease.…”
Section: Podocyte-specific Ko Of Fcrn Did Not Alter Neutrophil Invasisupporting
confidence: 89%
“…In addition, activated CD4 + T cells secreted IFNγ, IL-17, IL-2, and IL-6, but not IL-10, IL-4, or tumor necrosis factor-α. In mice, galectin-9 also mediated the decrease in Th1 and Th17 cell infiltration, which was associated with the downregulation of CXCL9, CXCL10, and CCL20 expression [11]. Elevated galectin-9 expression was also observed in SSc dermal fibroblasts in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies demonstrated that galectin-9 is distributed among tissues and induces various biological reactions such as cell aggregation, adhesion, chemoattraction, activation, and apoptosis [10]. Galectin-9 regulates the Th1/Th17 cell ratio to balance the immune response, thus playing a role in inflammatory diseases, and regulates T-cell immunity in chronic hepatitis C virus infection [11,12]. In addition, galectin-9 expression was reported to be significantly elevated in the serum and lesional skin of patients with SSc, it was also considered to contribute to the Th immune balance in the lesional skin of SSc [13].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, TIM‐3 signaling inhibition induces the expression of IFN‐γ, IL‐17, IL‐2 and IL‐6, but not IL‐10, IL‐4 or TNF‐α, in activated human CD4 + T cells . In animal studies, galectin‐9 seems to suppress the development, cytokine production and migration of Th1 and Th17 cells in a disease‐specific manner . Thus, galectin‐9 generally induces Th2 cytokine‐predominant immune imbalance by negatively regulating Th1/Th17 cells in inflammatory diseases.…”
Section: Activation Of Fibroblastsmentioning
confidence: 97%
“…116 In animal studies, galectin-9 seems to suppress the development, cytokine production and migration of Th1 and Th17 cells in a disease-specific manner. [117][118][119] Thus, galectin-9 generally induces Th2 cytokine-predominant immune imbalance by negatively regulating Th1/Th17 cells in inflammatory diseases. In SSc patients, galectin-9 is overexpressed in SSc dermal fibroblasts, and serum galectin-9 levels are significantly elevated and positively correlated with skin score in SSc patients.…”
Section: Ssc Dermal Fibroblasts Affect the Immune Responsementioning
confidence: 99%